The role of Uro-Vaxom in reducing infectious adverse effects and improving outcomes in bacillus Calmette-Guérin therapy for non-muscle-invasive bladder cancer - Sookyung Cho; Ho Seok Chung; Seung Il Jung; Do Gyeong Lim; Eu Chang Hwang; Dong Deuk Kwon (Investigative and Clinical Urology, 2025)
Purpose: Intravesical bacillus Calmette–Guerin (BCG) instillation is a cornerstone treatment for non-muscle-invasive bladder cancer (NMIBC) but is frequently associated with significant local and systemic adverse effects. This study aimed to investigate the effects of Uro-Vaxom (UVX) on BCG-related infectious adverse events and oncologic outcomes in patients with NMIBC. Materials and Methods: This retrospective cohort study included 251 NMIBC patients who underwent BCG induction therapy following transurethral resection of bladder tumors at a single institution. Patients were stratified into two groups: those not receiving UVX (non-UVX group, n=142) and those receiving UVX (UVX group, n=109). Clinical and oncologic parameters, including the frequency of antibiotic use, treatment discontinuation rates, and early recurrence rates following BCG therapy, were compared between the groups. Results: Antibiotic use during BCG treatment was significantly lower in the UVX group compared to the non-UVX group (p<0.001). Furthermore, BCG discontinuation due to urinary tract infection (UTI) was observed exclusively in the non-UVX group (p=0.003). Although tumor recurrence rates within one year were lower in the UVX group, this difference did not reach statistical significance (p=0.212). Multivariate analysis did not identify UVX use as a significant predictor of early recurrence or bacteriuria. Conclusions: The administration of UVX during BCG therapy in NMIBC patients was associated with reduced antibiotic use and a lower BCG discontinuation rate due to UTI, thereby improving treatment adherence. These findings highlight the potential role of UVX as a valuable adjunct to BCG therapy to optimize patient outcomes.